Multi-omics reveals goose fatty liver formation from metabolic reprogramming - Wei, Rongxue; Teng, Yongqiang; Han, Chunchun; Wei, Shouhai; Li, Liang; Liu, Hehe; Hu, Shenqiang; Kang, Bo; Xu, Hengyong (Frontiers in Veterinary Science, 2024)
To comprehensively provide insight into goose fatty liver formation, we performed integrative analysis of liver transcriptome, lipidome and amino acids metabolome, as well as peripheral adipose tissues transcriptome analysis using samples collected from the overfed geese and normally-fed geese. Transcriptome analysis showed that liver metabolism pathways were mainly enriched in glucolipid metabolism, amino acid metabolism, inflammation response and cell cycle; peripheral adipose tissue and the liver cooperatively regulated liver lipid accumulation during overfeeding. Liver lipidome patterns obviously changed after overfeeding, and 157 different lipids were yielded. In liver amino acid metabolome, the level of Lys increased after overfeeding. In summary, this is the first study describing the goose fatty liver formation from an integrative analysis of transcriptome, lipidome and amino acids metabolome, which will provide a whole new dimension to understand the mechanism of goose fatty liver formation.